Laparoscopic cholecystectomy. Treatment of choice for symptomatic cholelithiasis. - Schirmer, B D (1991)
Our initial experience with laparoscopic cholecystectomy (LC) for symptomatic cholelithiasis has involved 152 patients. Patient age ranged from 17 to 83 years; most were female (78%). Their average weight was 170 pounds (range, 75 to 365 lbs.). Twenty-two per cent had a single gallstone, while 9% had two to three stones and 64% had more than three stones. Exclusion criteria initially included upper abdominal scarring, severe acute cholecystitis, choledocholithiasis, and inability to tolerate general anesthesia. The first two of these are now only relative contraindications with increased experience. Thirteen of the one hundred fifty-two procedures (8.5%) required conversion to an open operation. Average time of operation was 138 minutes. Intraoperative cholangiography was attempted in 78% of cases and was completed successfully in 66% of those attempted. There have been no deaths. The complication rate has been low: 4% major, 0% life-threatening, and 7.2% minor complications. Postoperative analgesic requirements are remarkably low: 36% of patients required no narcotics after leaving the recovery room. Eighty-seven per cent of patients successfully undergoing LC were discharged by the first postoperative day. Most patients resumed normal activities within 1 week after discharge. Laparoscopic cholecystectomy offers the majority of patients with symptomatic cholelithiasis an improved treatment option, resulting in significantly less postoperative pain, hospitalization, and recuperation time.